A Study on the Role of Social Media Marketing in Promoting Adventure Tourism in Uzbekistan - Ikrom qizi , Ismoilova Go’zal (Miasto Przyszłości, 2023)
Adventure tourism is described as traveling to a place to engage in adventure activities in an environment that is natural. There are two types of adventure: soft adventure and hard adventure. Soft adventure activities include bird-watching, hiking, camping, and horseback riding, and they need little to no physical ability and expertise. Rock climbing, mountaineering, survival games, and caving are examples of hard adventure activities. Participants in hard adventure are more inclined to engage in physically and psychologically taxing outdoor activities. The aim of this article is to figure out what function social media platforms have in promoting adventure tourism in Uzbekistan. The research focuses on adventure tourism and associated items from the aforementioned places that should be marketed on social media. This report also suggests measures to boost adventure tourism.